2017
DOI: 10.18632/oncotarget.16882
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of CCL3/CCR5 axis in oral carcinogenesis

Abstract: The chemokine CCL3 is a chemotactic cytokine crucial for inflammatory cell recruitment in homeostatic and pathological conditions. CCL3 might stimulate cancer progression by promoting leukocyte accumulation, angiogenesis and tumour growth. The expression of CCL3 and its receptors CCR1 and CCR5 was demonstrated in oral squamous cell carcinoma (OSCC), but their role was not defined. Here, the functions of CCL3 were assessed using a model of chemically induced tongue carcinogenesis with 4-nitroquinoline-1-oxide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 53 publications
1
42
0
Order By: Relevance
“…18 The CCL3/CCR5 axis also promotes pro-tumorigenic effects in oral cancer. 19 Furthermore, CCR5 expression is associated with the recruitment of myeloid-derived suppressor cells in melanoma, promoting the tumour progression, 20 but this association was not being studied in HNSCCs. Additionally, polymorphisms in CCR5…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The CCL3/CCR5 axis also promotes pro-tumorigenic effects in oral cancer. 19 Furthermore, CCR5 expression is associated with the recruitment of myeloid-derived suppressor cells in melanoma, promoting the tumour progression, 20 but this association was not being studied in HNSCCs. Additionally, polymorphisms in CCR5…”
Section: Resultsmentioning
confidence: 99%
“…However, it was reported that the CCL5/CCR5 axis promotes the motility of oral cancer cells via upregulation of MMP‐9 production, suggesting its role in metastasis . The CCL3/CCR5 axis also promotes pro‐tumorigenic effects in oral cancer . Furthermore, CCR5 expression is associated with the recruitment of myeloid‐derived suppressor cells in melanoma, promoting the tumour progression, but this association was not being studied in HNSCCs.…”
Section: Discussionmentioning
confidence: 99%
“…In the combined model, in contrast to simple 4NQO induction, specific gene deletion or overexpression can be studied; compared with simple GEMMs, more specific OSCC can be induced, and genetic changes that are not directly carcinogenic can be investigated. This model can be used to study the role of miRNA (199,200), proteins (82, 184,203), and pathways (201,202) involved in the carcinogenesis of OSCC. Furthermore, the knock-in of green fluorescent protein can be used to label cells with specific gene changes (158,199).…”
Section: Nqo-induced Combined With Gemmsmentioning
confidence: 99%
“…In the gene ontology (GO) analysis using these 233 genes, migrationrelated GO terms were dominant (Additional file 1: Figure S8), which is consistent with the role of EICD in cell motility. Notably, several chemokine ligands (CCL3, CCL20, and CXCL2), widely studied as mediators of epithelialmesenchymal transition, tumorigenesis, and metastasis [31][32][33][34][35], were increased ( Fig. 5a) and top-ranked in terms of the fold increase (Additional file 2: Table S1).…”
Section: Eicd Induces Changes In Gene Expressionmentioning
confidence: 99%